BAITUL MAL ACEH DALAM PERSPEKTIF KONSEP WELFARE STATE - Novita Sari; Nurul Fajri; Muliawati; Maghfira Faraidiany (Journal Publicuho, 2023)
This study aims to test and find out whether the concept of Baitul Mal management in Aceh has similarities or not with the concept of the welfare state. The researcher used the literature study method by reading and doing various things, especially existing literature, and carrying out a content analysis approach. The literature in question is that which has a relationship with the research problem. The results of the study show that the management of the Baitul Mal in Aceh has similarities with the concept of a welfare state, which means that the state has a great responsibility towards its citizens to be prosperous and prosperous, both in the education, health and social sectors through guarantees such as insurance or others. The concept of the welfare state aims to reduce poverty through government policies and anticipate criminal acts, which of course, make the country unstable.